1987
DOI: 10.1002/bsl.2370050103
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of adolescents charged with homicide: Review of 72 cases

Abstract: The present study examined a comparatively large sample of 72 adolescents charged with murder who were referred for pretrial evaluation in the State of Michigan over a 9-year period. Subjects are compared with a control group of 35 adolescents charged with nonvwlent larceny offenses. Information regarding the adolescents' demographic and social bQckground, and the circumstances of the offense, are presented. Recognition of the diverse motives and circumstances of adolescent homicide may help to explain discrep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 15 publications
(5 reference statements)
2
46
0
1
Order By: Relevance
“…As importantly, the current results suggested that an 'escalation' model [see Cornell et al, 1987b] may be helpful in understanding how adolescent's violence increases over time. A chapter by Loeber et al [2005a] described an ''overt trajectory,'' which posited that violent behavior increased over time starting with minor aggression and ending in severe violence.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…As importantly, the current results suggested that an 'escalation' model [see Cornell et al, 1987b] may be helpful in understanding how adolescent's violence increases over time. A chapter by Loeber et al [2005a] described an ''overt trajectory,'' which posited that violent behavior increased over time starting with minor aggression and ending in severe violence.…”
Section: Discussionmentioning
confidence: 90%
“…Some had extensive histories of juvenile delinquent behavior and the homicide represented the culmination of many delinquent acts'' (p 19). Cornell et al [1987b] idea of an ''escalation hypothesis'' where the early engagement in criminal behavior leads to more significant antisocial behavior is highly consistent with the life-course persistent (LCP) typology [Moffitt, 1993; see also Moffitt, 2003]. Individuals with LCP have a poorer prognosis and their behavior tends to be related to neurological impairment.…”
Section: The Roles Of Early Criminal Behavior and Criminal Versatilitmentioning
confidence: 92%
See 2 more Smart Citations
“…Tötungsdelinquenten beispielsweise im Allgemeinen einen unauffälligen Kontakt zu Gleichaltrigen (Hinrichs et al, 1997) und sind signifikant seltener psychiatrisch behandelt worden und unauffälliger als eine gleichaltrige Kontrollgruppe (Cornell, Benedek & Benedek, 1987; s. auch Dolan & Smith, 2001 (Beckmann & Gollwitzer, 1987;Reilmann, 1989). Personen mit negativem Selbstbild neigen dabei zu illusorisch positiver Selbsteinschätzung in der Abwägungsphase, nicht aber der Planungsphase, während dies bei Personen mit positiver Selbstsicht umgekehrt der Fall ist (Bayer & Gollwitzer, 2005 …”
Section: Studienbefunde Zu Amoktätern Im Erwachsenenalterunclassified